Ambient PM2.5 and birth outcomes: Estimating the association and attributable risk using a birth cohort study in nine Chinese cities. (May 2019) - Liang, Zhijiang; Yang, Yin; Qian, Zhengmin; Ruan, Zengliang; Chang, Jenjen; Vaughn, Michael G.; Zhao, Qingguo; Lin, Hualiang
Abstract: Background: Previous studies have reported that maternal exposure to particles with aerodynamic diameter <2.5 μm (PM2.5 ) is associated with birth outcomes. However, a multicity birth cohort study has not been conducted in China, and the attributable fraction of adverse birth outcomes due to PM2.5 exposure remains unknown. Methods: We examined associations in a birth cohort of 1, 455, 026 mother-and-live-birth pairs who were followed up from the first hospital visit for pregnancy until the birth of the baby during 2014–2017 in nine cites of the Pearl River Delta (PRD) region, China. The PM2.5 exposures were estimated based on the air pollution concentrations of the nearby monitors. Cox proportional hazards regressions were employed to examine the associations. Results: We found 1% (HR = 1.01; 95% CI: 1.00, 1.02), 6% (HR = 1.06; 95% CI: 1.05, 1.07), and 7% (HR = 1.07; 95% CI: 1.06, 1.08) increases in risk of PTB and 20% (HR = 1.20; 95% CI: 1.18, 1.22), 18% (HR = 1.18; 95% CI: 1.15, 1.20), and 20% (HR = 1.20; 95% CI: 1.17, 1.23) increases in risk of LBW, with each 10 μg/m 3 increase in PM2.5 from trimester 1 to trimester 3, respectively. For PTB, highest HRs were observed during trimester 3, as for LBW, stronger effect were observed during trimester 1 and trimester 3. We further estimated that 7.84% (95% CI: 6.21%, 9.50%) of PTB and 14.85% (95% CI: 13.00%, 16.61%) of the LBW cases could be attributable to PM2.5 exposure during the third trimester. Conclusion: The results indicate that maternal PM2.5 exposure is a risk factor for both LBW and PTB, and responsible for considerable burdens of PTB and LBW in the Pearl River Delta region. Highlights: We examined the effects of PM2.5 on preterm birth and low birth weight. PM2.5 exposure was found to be associated with increased risk of preterm birth. PM2.5 exposure was observed to be associated with increased risk of low birth weight. Substantial burden of preterm birth and low birth weight could be attributable to PM2.5 exposure.